ANALISIS PENERAPAN WITHHOLDING TAX SYSTEM TERHADAP PAJAK PENERANGAN JALAN DI KAB. MINAHASA UTARA PADA PT. PLN (PERSERO) WILAYAH SULUTTENGGO - Tanod, Sendi; Saerang, David; Pontoh, Winston (Universitas Sam Ratulangi, 2018)
Street lighting tax is territorial tax which is paid by the tax payer as electricity supplier, street lighting tax is collected at the same times with electricity bill payment by PLN customers. The purpose of this research is to analyze the application of withholding tax system in terms of cutting, deposit and reporting of Street Lighting Tax by PT. PLN (Persero) Area Suluttenggo. This research uses descriptive analysis method, which is done by interview and documentation. The results of the study show the Road Lighting Tax in the District North Minahasa by PT. PLN (Persero) Area Suluttenggo Region has been in accordance with the Law No.28 of 2009 and regent of the District north Minahasa No.34 of 2016. For liquefaction road tax refund shall be remitted to the regional treasury through a bank Sulut and in a few months in 2016 there shall be a delay in depositing which is not in accordance with the due date of the fifteenth of the ensuing month, in the case of reporting of PT. PLN (Persero) Area Suluttenggo Region has included Local Tax Payer (SSPD) for each month.Keywords: tax holding system, street lightning tax